Uso de minerales orgánicos en la alimentación de pollos de engorde - Cañarte Velásquez, Luis Brayan (2019)
Organic minerals are composed of amino acid carbohydrates and proteins that have great bioavailability in feeding broilers compared to inorganic ones, improving consumption and digestibility in chickens. The research aimed to generate published information on the use of organic minerals in the feeding of broilers. This documented research work was developed based on the collection of articles, journals, and experimental works. The information was collected between the months of June and August of 2019. The methods that helped to gather informed information were analysis and response, these allowed to obtain results from published works, written online. He also had an emphasis on experimental literature and documentary research, which have shown the benefits of using organic minerals in the feeding of chickens to productive behavior. The minerals are intertwined more quickly which makes transport easier, giving improvements in physiological and metabolic development, presence of selenium in birds improved reproductive parameters and intestinal integrity, On the other hand, they reported that by including 100% of Organic minerals (zn, mg) in the diet, decreased by 13.5% of the loss in excretion and daily gains greater than 3% equivalent to 300g were achieved The use of minerals not only contributes to the profitability of a broiler company, but also has a great impact on the environment by reducing the excretion of feces without causing negative effects on production.